Alterations in upper airway cross-sectional area in response to lower body positive pressure in healthy subjects. Issue 10 (18th April 2007) - Shiota, Satomi; Ryan, Clodagh M; Chiu, Kuo-Liang; Ruttanaumpawan, Pimon; Haight, James; Arzt, Michael; Floras, John S; Chan, Christopher; Bradley, T Douglas
Abstract : Background: Fluid accumulation in the neck during recumbency might narrow the upper airway (UA) and thereby contribute to its collapse in patients with obstructive sleep apnoea (OSA). It is hypothesised that acute fluid shifts from the legs to the upper body in healthy subjects would increase neck circumference and reduce the cross-sectional area of the UA (UA-XSA). Methods: In 27 healthy non-obese subjects of mean (SE) age 39 (3) years and body mass index 23.2 (0.6) kg/m 2 studied while supine, leg fluid volume was measured using bioelectrical impedance, neck circumference using a mercury strain gauge and mean UA-XSA between the velum and the glottis using acoustic pharyngometry at end expiration. Measurements were made at baseline after which subjects were randomly assigned to a 5 min time control period or to a 5 min application of lower body positive pressure (LBPP) at 40 mm Hg by anti-shock trousers, separated by a 15 min washout period. Subjects then crossed over to the opposite arm of the study. Results: Compared with control, application of LBPP significantly reduced leg fluid volume (p<0.001) and increased neck circumference (p<0.001), both at 1 min and 5 min, and reduced UA-XSA after both 1 min (−0.15 cm 2 ; 95% CI −0.23 to −0.09, p<0.001) and 5 min (−0.20 cm 2 ; 95% CI −0.33 to −0.09, p<0.001). Conclusion: In healthy subjects, displacement of fluid from the legs by LBPP causes distension of the neck and narrowing of the UA lumen. Fluid displacement from the lower to the upper body while recumbent may contribute to pharyngeal narrowing and obstruction to airflow in patients with OSA. This may have particular pathological significance in oedematous states such as heart and renal failure.